Incidencia de enfermedades dermatológicas y su relación con lesiones papulares eritematosas en menores de 5 años en el Centro de Salud La Maná durante el segundo semestre 2014 - Castillo Escudero, Liliana Natali (2015)
Skin diseases vary widely with geographical location and probably are influenced by ethnic and environmental factors are also present major cause of morbidity, economic loss and social exclusion. In developing countries, dermatological diseases are a major public health problem, mainly of infectious origin. Infections of the skin and subcutaneous tissue with superficial mycoses are the main reasons for dermatological consultation in children appearing diseases likefungal infections, impetigo, furuncle, carbuncle, cellulitis and other superficial skin infections, scabies, dermatitis, pruritus, disorders of the skin adnexa, skin cancers, psoriasis, insect bites and other. In Ecuador dermatological diseases affect 30% of children under 5 years in addition to the consultations in outpatient pediatric dermatological problems mainly due to seborrheic dermatitis child is more relevant in the neonatal period and infancy. Our study is focused on analyzing the dermatological diseases and their relationship with erythematous papular lesions in children under 5 years treated at the Health Center La Maná, during the second half of 2014, to identify risk factors and decrease the numbers of cases of skin lesions. Keywords: skindiseases, erythematouspapularlesions, papula, macula, viral rashes, urticaria.